Adsorption of hexavalent chromium from water using graphene oxide/zinc molybdate nanocomposite: Study of kinetics and adsorption isotherms - K. S., Merija; Rahulan, K. Mani; Sujatha, R. Annie; Little Flower, N. Angeline (Frontiers in Energy Research, 2023)
Hexavalent chromium is one of the most hazardous contaminants that threaten the environment. The present research work involves the synthesis of Graphene Oxide/Zinc molybdate (GO/ZM) nanocomposite by wet chemical route. The structure and morphology of the synthesized samples were analysed by various characterization techniques such as X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), UV-Vis Spectroscopy, and High-Resolution Transmission Electron Microscopy (HR-TEM), Brunauer-Emmett-Teller (BET) surface area analysis, Barrett-Joyner-Halenda (BJH) pore size analysis and Raman Spectroscopy. The efficiency of the prepared samples for removing hexavalent chromium from the water was investigated by performing batch adsorption studies. The maximum adsorption capacity was optimum at using 6 mg adsorbent, under conditions pH 2 with contact time for 120 min and temperature 283 K. Two isotherm models and two kinetic models were used to study the adsorption mechanism of Cr(VI) ions adsorption on the surface of GO/ZM nanocomposite. The results of isotherm and kinetic modelling shows that the adsorption of Cr(VI) using GO/ZM nanocomposite was well described by Freundlich Isotherm model with higher correlation coefficient (R2 = .985) and follows pseudo second order kinetic model.